Scratch! um estudo de caso - Bressan, Manuelle Lopes Quintas (2016)
The study aimed to analyze how and if a Visual Programming Environment can contribute by supporting the creative processes of adolescents, an auxiliary tool for learning by problem solving, encouraging new ways of using ICT in education. This study is justified by the need to deepen the issues related to the use of ICT in Basic Education teachers and not only the use of projectors and videos to replace the chalkboard, or research tools in search engines only to convey information in order to favor traditional teaching methodologies. As a research methodology was chosen qualitative approach to interpretation, the study of case type. The seizure of the data was in experimental field through socio-educational and daily quiz board, followed by analysis of content and description of the results obtained. Study participants were adolescents from 13 public and private elementary schools and high school in the city of Araucaria-Pr. The study showed the development of higher psychological functions, computational thinking in students such as attention, memory and perception. These skills were observed during the preparation of projects, through the comprehension skills, planning, retrospect and development of individual and collective strategies to solve the problems encountered. This study differs from others already undertaken with Scratch therefore emphasizes the pursuit of freedom and creativity of the subjects students in developing their own projects, as a strategy for autonomy.